Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 14 FRIENDLY VISITS OF INQUIRY. Eligible for treatment, continued to attend (of these, three were recommended to join clubs) 4 Subsequently became C.O.S. cases 2 Referred to Clergy 1 — 3 Advised by friendly visitor to some purpose 2 Nothing further done 1 Did not return. Refused to give particulars 2 Found able to pay a general practitioner 1 „ „ „ „ a specialist 1 Case lapsed, as patient did not return 1 — 5 15 FRIENDLY VISITS. Cases advised by friendly visitor to some purpose 5 Subsequently became C.O.S. cases :— Assisted 6 Not assisted 2 Withdrawn 1 — 9 Nothing further came of the visit 4 Reports not yet received 2 20 I have already sent in a detailed report of Friendly Visits and Partial Inquiries up to June 17. The following are examples of cases since that date :— INQUIRIES. A. S. — Stated he was an undertaker's assistant; wages 10s. and commission. Wife, two grown-up daughters (delicate), and five other children dependent. Sent 7s. 6d. Report from partial inquiry (of employer). Man's wages were 28s.— 30s. a fair average the year round — and besides this receives a gratuity for each funeral from the clients. Caretaking at the shop, and so lives rent free. Two daughters at work. Action of hospital.— Man considered able to pay, and would certainly have been sent away had he returned; he did not do so. W. S.— Patient first came in 1900; then stated he was a 'bus driver, earning nearly £2, and that the wife kept a domestic agency ; three children dependent. Rent 20s.; nothing let off. Sent away, considered able to pay. Came again September 26, 1901 ; stated he had never been before ; that he was an odd man at tram driving, 4s. 9d. per day. Wife was delicate, unable to work ; one child dependent. Rent 5s., one room. Gave quite a different address. Report from partial inquiry.— False addresses given as to dwelling ace [place] and employer. Action of hospital.— Nothing further done, as man did not return. 378/IMSW/A/1/1/9